EMPOWERING STUDENTS’ INTEGRATED LANGUAGE SKILLS THROUGH THE USE OF TEACHERS’ LEARNING VIDEOS IN BLENDED LEARNING CLASS - Leli Rahmawati; Ruminda Ruminda; Juhana Juhana (Indonesian EFL Journal, 2023)
Integrated language skills that applied with ITC-based learning is very important to teach as it helps students to be familiar to communicate English in the real situations. Meanwhile learning videos are part of ITC that are highly effective and efficient to help students to understand learning materials as well. The new normal era after the pandemic seems engaging both teachers and students to use learning videos in blended learning class which consists of varied learning interactions. The blended learning gives both teachers and students more opportunities to apply advanced technologies, so they get ready in facing society 5.0 era. This research is a case study of mixed method design. It aims to find out qualitatively and quantitatively to what extent the use of teachers’ learning videos in blended learning empower students’ integrated language skills. By doing questionnaires, interviews and having observation on 32 participants-the 2 teachers and 30 students of MTs. Negeri 6 Cianjur at the eighth grade, the data were collected and analyzed. The findings revealed that positive respond to the use of teachers' learning videos in MTs. N 6 Cianjur reached 81%, the use of blended learning class was 80% and students' integrated learning skills empowerments was 79%. These values are then averaged to 80%. Thus quantitatively the extent of students' integrated language skills empowerment through the use of teachers' learning videos in blended learning class is feasible. While the results of qualitative data analysis obtained from semi-structured interviews show that the data obtained can expand and deepen the quantitative data.Keywords: blended learning; integrated language skills; learning videos; students’ empowerment.